Peningkatan Berat Badan pada Bayi (3-6 Bulan) Melalui Infant Exercise - I Ketut Sudiana; Yuni Sufyanti Arief; Puteri Indah (Universitas Airlangga, 2007)
Introduction: Infant body weigth is used as a best indicator to measure infant growth and nutritional status. Body weight that not related on age, does not gain at least 500-600 gram for about three months, or over body weight, can be used to predict heath problem. Infant exercise stimulation is an effort to increase body weight so that infant gain on a normal pattern of weight. The objective of this study was to analyze the influence of infant exercise to weight gain related on age on infant (3-6 month). Method: A quasy-experimental non-randomized control group pre-posttest design was used in this study. The subjects were infants in 3-6 month aged lived in Wates Negoro and Manduro village, Subdistrict Ngoro, Mojokerto. There were 14 infants who met to the inclusion criteria. Data were collected by using body weight observation scale after infant exercise had been done for 4 week. Data were analyzed by using Independent t-Test and Paired t-Test with significance level of α≤0.05. Result: Result showed that infant exercise had effect on weight gain related on age on infant (3-6 month). Paired t-Test to the treatment group showed a significant differences between pre test and post test (p=0.00000). Control group showed a significant differences between pre test and post test (p=0.00005). Independent t-Test in pre test showed body weight (p=0.74) and increasing of body weight (p=0.000). Discussion: It can be concluded that there were significant effect of infant execise to weight gain related on age on infant (3-6 month). The limitation was that quality and quantity of the infant’s nutrition can not be controlled by the researcher.